A clinical diagnostic algorithm for early onset cerebellar ataxia. (September 2019) - Brandsma, R.; Verschuuren-Bemelmans, C.C.; Amrom, D.; Barisic, N.; Baxter, P.; Bertini, E.; Blumkin, L.; Brankovic-Sreckovic, V.; Brouwer, O.F.; Bürk, K.; Catsman-Berrevoets, C.E.; Craiu, D.; et al.
Abstract: Early onset cerebellar Ataxia (EOAc) comprises a large group of rare heterogeneous disorders. Determination of the underlying etiology can be difficult given the broad differential diagnosis and the complexity of the genotype–phenotype relationships. This may change the diagnostic work-up into a time-consuming, costly and not always rewarding task. In this overview, the Childhood Ataxia and Cerebellar Group of the European Pediatric Neurology Society (CACG-EPNS) presents a diagnostic algorithm for EOAc patients. In seven consecutive steps, the algorithm leads the clinician through the diagnostic process, including EOA identification, application of the Inventory of Non-Ataxic Signs (INAS), consideration of the family history, neuro-imaging, laboratory investigations, genetic testing by array CGH and Next Generation Sequencing (NGS). In children with EOAc, this algorithm is intended to contribute to the diagnostic process and to allow uniform data entry in EOAc databases. Highlights: This algorithm will guide the clinician through the diagnostic process of EOA. We provide clear phenotypic descriptions to target genetic investigations. The reader will obtain an overview of known genetic causes.